The Endocrine Society's 92nd Annual Meeting, June 19–22, 2010 - San Diego 2010
DOI: 10.1210/endo-meetings.2010.part3.or2.or42-4
|View full text |Cite
|
Sign up to set email alerts
|

Partial Sleep Restriction Decreases Insulin Sensitivity in Type 1 Diabetes.

Abstract: OBJECTIVE -Sleep restriction results in decreased insulin sensitivity and glucose tolerance in healthy subjects. We hypothesized that sleep duration is also a determinant of insulin sensitivity in patients with type 1 diabetes.RESEARCH DESIGN AND METHODS -We studied seven patients (three men, four women) with type 1 diabetes: mean age 44 Ϯ 7 years, BMI 23.5 Ϯ 0.9 kg/m 2 , and A1C 7.6 Ϯ 0.3%. They were studied once after a night of normal sleep duration and once after a night of only 4 h of sleep. Sleep charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 6 publications
4
46
2
3
Order By: Relevance
“…These findings are consistent with epidemiological studies showing that poor sleep quality and both short and long sleep duration are associated with higher glycated haemoglobin (HbA 1c ) levels in adults with type 2 diabetes [3,5,12,13]. Also in adults with type 1 diabetes, experimental partial sleep restriction lowers insulin sensitivity [14]. In another study, short sleep duration measured by wrist actimetry has been shown to be associated with a 0.64% (7 mmol/mol) increase in HbA 1c level in adults with type 1 diabetes [15], while selfreported sleep duration and sleep quality showed no relation with HbA 1c [9].…”
Section: Introductionsupporting
confidence: 90%
“…These findings are consistent with epidemiological studies showing that poor sleep quality and both short and long sleep duration are associated with higher glycated haemoglobin (HbA 1c ) levels in adults with type 2 diabetes [3,5,12,13]. Also in adults with type 1 diabetes, experimental partial sleep restriction lowers insulin sensitivity [14]. In another study, short sleep duration measured by wrist actimetry has been shown to be associated with a 0.64% (7 mmol/mol) increase in HbA 1c level in adults with type 1 diabetes [15], while selfreported sleep duration and sleep quality showed no relation with HbA 1c [9].…”
Section: Introductionsupporting
confidence: 90%
“…In the early part of the day, after 2 days of short bedtimes, glucose levels were higher and insulin levels were lower than after 2 days of longer bedtimes. These findings have since been replicated in other studies that have shown that sleep deprivation can lead to insulin dysregulation [84][85][86].…”
Section: Metabolismsupporting
confidence: 61%
“…control in t. 1 diabetes function, and neuro-hormonal regulation (21)(22)(23)(24)(25)(26). Concerning specifically T1DM, a study revealed that a single partially deprived night is enough to produce insulin resistance (27). In this study individuals were allowed to sleep for 4 hours at night, and in the following day their insulin sensitivity was reduced in 14-21%.…”
Section: Discussionmentioning
confidence: 84%